2013
DOI: 10.1063/1.4821610
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of mechanisms for He-I emission radial profile broadening in a weakly ionized cylindrical helium plasma with recombining edge

Abstract: Spatially resolved spectroscopic measurements of He-I line emission are used to study the causes of emission profile broadening radially across the cylinder of a weakly ionized helium plasma. The plasma consists of an ionizing core (r < 2 cm) surrounded by a recombining edge (r > 2 cm) plasma. The brightness profiles of low-n EUV He-I resonance lines are shown to be strongly radially broadened due to opacity. The brightness profiles of high-n visible lines are also found to be strongly radially broadened, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 28 publications
(32 reference statements)
1
21
0
Order By: Relevance
“…3(a, b)], due to the tendency of probe characteristics to overestimate ! in these plasmas [20]. A shortcoming of this method is that the fraction of He-II emission due to thermal electrons (vs thermal + non-thermal electrons) is not known a-priori; however, the resulting error bars are small: red curves in Fig.…”
Section: Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…3(a, b)], due to the tendency of probe characteristics to overestimate ! in these plasmas [20]. A shortcoming of this method is that the fraction of He-II emission due to thermal electrons (vs thermal + non-thermal electrons) is not known a-priori; however, the resulting error bars are small: red curves in Fig.…”
Section: Measurementsmentioning
confidence: 99%
“…Figure 3(c) shows the calculated helium density profile, showing some (~50%) hollowing on center. This is calculated using a Monte-Carlo simulation of helium neutral trajectories in the cylindrical vacuum chamber [20]. The simulation uses the experimentally measured !…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…To perform the Abel transform, the electron temperature and electron density measured by a Langmuir probe were used. However, diagnosis of a low electron temperature plasma using a Langmuir probe has difficulties with anomalous I − V characteristics [12,13]. Therefore, the electron temperature obtained by a Langmuir probe, T p e , was substituted with the electron temperature T B e from the Boltzmann plot in the peripheral region, where the emission intensity from highly excited atoms becomes strong.…”
Section: Resultsmentioning
confidence: 99%
“…Plasma blob has a filamentary structure along the magnetic field line and has a higher density than the SOL plasma. Interestingly, the cross-filed plasma transport, which could be associated with plasma blob-like structure, was found to be enhanced in the detached plasma condition in linear plasma devices [4][5][6], helical devices [7], and tokamaks [8,9]. In the linear plasma device NAGDIS-II (NAGoya DIvertor plasma Simulator II), fast framing camera observations have revealed that a spiral structure ejected from the plasma column was rotated in E × B direction in the peripheral region of the plasma column, where the electric field was in the radial direction [4,10].…”
Section: Introductionmentioning
confidence: 99%